The legend of Lakshmi Prasad - Khanna, Twinkle (b, 2016)
A gangly young girl transforms her village with a revolutionary idea. Sixty-eight year old Noni Appa finds herself drawn to a married man. Bablu Kewat becomes opbsessed with sanitary napkins much to his family's horror, and a young woman keeps checking the weather forcast as she meticulously plans each of her five weddings."--Publisher's description.
Keywords: Villages -- Humor. -- India; Interpersonal relations -- Fiction; Compulsive behavior -- Fiction